PENGEMBANGAN PLASTIK WRAP (PLA-PCL) RECYCLABLE DENGAN PENAMBAHAN MINYAK SEREH WANGI SEBAGAI AGEN ANTI BAKTERI - Aida Safitri (Politeknik Negeri Lhokseumawe, 2020)
Research on the development of plastic wrap cellulose nanocrystals (CNC) aims to study the elasticity and anti-bacterial properties of the plastic produced. Functionally, CNC is needed to increase the dispersion of the nanofiller in the polymer matrix and influence the final properties of the nanocomposites. The method used for the particle dispersion process is the grafting method. This method integrates the chemical structure of the monomer grafted onto cellulose which will affect the properties of grafted cellulose such as hydrophilic and hydrophobic characters, increased elasticity, absorption of dyes and water, the ability to exchange ion and heat resistance. Another material added is Poly ε-caprolactone (PCL) because it is an interesting biodegradable polymer and has been widely used because it increases the flexibility of PLA, avoids the effect of plasticizers during processing and avoids the phenomenon of migration. The novelty of this research is the addition of fragrant lemongrass oil as an anti-bacterial agent. Chemical components such as geraniol and linalol are the main components that act as anti-bacterial agents based on positive and gram-negative bacterial tests using Bacillusubtilis, Staphylococcus epidermidis, Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumonia and Escherichia coli. To determine the final properties of the product in the form of recyclable plastic wrap, mechanical tests such as thermal resistance (TGA), XRD, tensile strength and SEM were performed. The results of these tests will be used as parameters prior to their application in the extractive industry.Keywords— Citronella, Plastic, PLA, PCL, Plasticizer